1999
DOI: 10.1007/s007920050111
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a chymotrypsinogen B-like enzyme from the archaeon Natronomonas pharaonis and other halobacteria

Abstract: A protease of a molecular mass of approximately 30kDa was isolated and purified from the haloalkaliphilic archaeon Natronomonas (formerly Natronobacterium) pharaonis. The enzyme hydrolyzed synthetic peptides, preferentially at the carboxyl terminus of phenylalanine or leucine, as well as large proteins. Hydrolysis occurred over the range of pH from 6 to 12, with an optimum at pH 10. The temperature optimum was 61 degrees C. The enzyme was nearly equally active over the range of salt concentration from 0.5 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…All 15 previously published N. pharaonis genes could be identified within the genome, although minor sequence variations were detected usually owing to strain differences. However, a partially sequenced protease from N. pharaonis, which is extremely similar to vertebrate chymotrypsin (Stan-Lotter et al 1999), could not be found.…”
Section: Function Analysismentioning
confidence: 96%
“…All 15 previously published N. pharaonis genes could be identified within the genome, although minor sequence variations were detected usually owing to strain differences. However, a partially sequenced protease from N. pharaonis, which is extremely similar to vertebrate chymotrypsin (Stan-Lotter et al 1999), could not be found.…”
Section: Function Analysismentioning
confidence: 96%
“…In comparison, haloalkaliphilic bacteria have been relatively less attended, as only few alkaline proteases are reported from these organisms (Studdert et al 1997;Stan-Lotter et al 1999;Gimenez et al 2000;Studdert et al 2001;Polosina et al 2002). Besides the novel catalytic applications, the wide occurrence of many of such enzymes among the haloalkaliphilic bacteria holds ecological significance.…”
Section: Introductionmentioning
confidence: 94%
“…Protease production has been shown in several species of halophilic archaea including Halobacterium salinarum (Izotova et al 1983;Ryu et al 1994;Kim and Dordick 1997); Natrialba asiatica (Kamekura and Seno 1990;Kamekura et al 1992), Haloferax mediterranei (Stepanov et al 1992;Kamekura et al 1996;Nolasco et al 2002); Natronomonas pharaonis (Stan-Lotter et al 1999); Natronococcus occultus (Studdert et al 1997(Studdert et al , 2001; Natrialba magadii (Giménez et al 2000), Halogeometricum borinquense (Vidyasagar et al 2006) as well as in Halobacterium sp. SP1 (1) (Akolkar et al 2008) and Natrinema sp.…”
Section: Introductionmentioning
confidence: 96%